MgO Thin Film Growth on S (001) by Radio-Frequency Sputtering Method - Singh, Jitendra Pal; Kumar, Manish; Lim, Weon Cheol; Lee, Hyun Hwi; Lee, Young Mi; Lee, Sangsul; Chae, Keun Hwa (AMER SCIENTIFIC PUBLISHERS, 2020)
Herein, sputtering duration and annealing temperature effects on the structure and local electronic structure of MgO thin films were studied using synchrotron radiation based X-ray diffraction and X-ray absorption spectroscopic investigations. These films were grown at substrate temperature of 350 degrees C by varying sputtering duration from 25 min to 324 min in radio frequency (RF) sputtering method followed by post-deposition annealing at 400, 600 and 700 degrees C for 3 h. These films were amorphous upto certain sputtering durations, typically upto 144 min and attains crystallization thereafter. This kind of behavior was observed at all annealing temperature. The textured coefficient of crystalline films envisaged that the orientation was affected by annealing temperature. Coordination of Mg2+ ions was more distorted in amorphous films compared to crystalline films. Moreover, onset of molecular oxygen are absorbed at low annealing temperature on these films.
Keywords: ABSORPTION FINE-STRUCTURE; MOLECULAR-BEAM EPITAXY; MAGNESIUM-OXIDE MGO